Endometrial osteopontin, a ligand of β3-integrin, is maximally expressed around the time of the “implantation window” - Wolff, Michael von; Strowitzki, Thomas; Becker, Veronika; Zepf, Claudia; Tabibzadeh, Siamak; Thaler, Christian J (Fertility and sterility, 2001)
To analyze endometrial mRNA and protein expression of osteopontin and its receptor, β3-integrin, throughout the menstrual cycle. Design: Study by immunohistochemistry, RNase protection assay, and ELISA.
Gesehen am 20.11.2020